Highly porous ZrO2 cellular ceramics with 3D network architecture. Issue 6 (15th April 2020) - Liu, Jingjing; Yang, Haocheng; Ren, Bo; Rong, Yedong; Xi, Xiaoqing; Lu, Yuju; Zhao, Yi; Yang, Jinlong
Abstract: Cellular ceramics with 3D network architecture are attracting ever-increasing attention because of their great application potential in multiple fields. Unfortunately, a daunting challenge still remains for fabricating such materials. A novel methodology is provided in the current work to construct cellular ZrO2 ceramics with such architecture by combining polyurethane foaming and chemical modification technology. Stearic acid grafted ZrO2 powder with improved dispersibility allows the successful assembly into the polyurethane porous framework. The obtained cellular materials possess a three-dimensional network architecture with windows on the cell wall. The resulting ZrO2 cellular ceramic with such unique structure exhibits a relatively high porosity (83.5%) and robust compressive strength (13.5 MPa), which outperforms most of the existing ZrO2 -based counterparts. With above advantages, we envision that as-prepared products are promising for filter applications.